Penerapan Metode Design Thinking Pada Model Perancangan Ui/Ux Dengan Usability Testing Untuk Sistem Akademik Sekolah Dasar - Aditya.P, Praditama; Djumhadi, Djumhadi (Prosiding, 2024)
This study examines the implementation of Design Thinking in the UI and UX design model of an elementary school academic system, and evaluates its quality through usability testing based on ISO 9241-11. Design Thinking is a user-centered approach that aims to understand the needs and challenges faced by users such as students, teachers, and parents. The process involves five stages: empathize, define, ideate, prototype, and test. The resulting prototype was tested using usability testing, with ISO 9241-11 as a reference to measure effectiveness, efficiency, and user satisfaction. The findings indicate that Design Thinking can produce UI/UX designs that are more intuitive and responsive to user needs. Evaluation based on ISO 9241-11 demonstrates that the designed system meets the expected quality standards, with high scores in effectiveness, efficiency, and user satisfaction. Consequently, this study concludes that when appropriately implemented and tested against ISO 9241-11, Design Thinking can significantly enhance the quality of UI/UX design in elementary school academic systems.